Mechanical properties and morphology of nitrile butadiene rubber (NBR) with nano cellulose crystal / Lye Ying Jie - Lye, Ying Jie (2019)
Nitrile Butadiene rubber is blending with different ratio of nanocellulose crystal ranging from 0.2phr to 4 phr and dilute with other chemical additive which is naphthalene sulphonic acid formaldehyde or sodium dodecylbenzenesulphonate (SDBS) to improve its properties. Surface tension, zeta potential and instability index for compounded nitrile before drying is measured. The morphology and physical properties of nanocellulose blending with compounded nitrile was investigated. The scanning emission microscopy (SEM) showed there is a rough surface of nanocellulose in nitrile latex. The tensile result indicated that there was an increase in result of tensile strength by dose in nanocellulose in nitrile butadiene rubber compound. However, there is a decrease of tensile properties when the nanocellulose in nitrile butadiene rubber is up to 4phr.This study reveal that the dispersion of nanocellulose in nitrile butadiene is crucial to optimize the dosage versus improve properties.